Religie świata i ich stanowisko wobec eutanazji - Skura-Madziała, Anna (Annales. Etyka w Życiu Gospodarczym, 2009)
The attitude towards death and dying reflects the society’s view on a human being as a subject. Due to the progress in medical science a growing interest has been observed in the problem of death, including the right to dignified dying. One of the issues connected with the phenomenon of dying is the problem of euthanasia seen as one’s right to decide on one’s own death in extreme cases. The question of the legality of euthanasia is becoming a subject of consideration more and more often, which is a result of a celebratory culture of death and the obsolescence of faith and religious practice. The aim of the following report is to show the attitude of major religions of the world towards euthanasia. What arguments of religious nature are against the legality of mercy killing? Both Christian and non-Christian religions rise to speak on the matter. All religions stress their veto over mercy killing, justifying their view in various ways. Christians claim that God is the donor and lord of life; a man cannot decide on ending human life as he or she is only the user, not the owner of it. Judaism assumes that human life has an absolute value, is sacred, untouchable, as God’s gift. Islam, quoting Koran, also preserves life as God’s gift. According to Buddhist ethics, the annihilation of both one’s own and someone else’s life is the worst of evil deeds. Will the arguments of religious nature mean enough to stop the legality of euthanasia?